Determinants on demands of life insurance among employees at Kotra Pharma Malacca / Nazirah Kamaruddin and Fatin Syamimi Abdul Malek - Kamaruddin, Nazirah; Abdul Malek, Fatin Syamimi (Faculty of Business and Management, 2013)
The purpose of this study is to determine the demands of life insurance among employees at Kotra Pharma Malacca. For this study only 200 of respondents which are employees of Kotra Pharma Malacca were selected using simple random sampling. The objectives of this study aim’s to identify the determinants on demands of life insurance among employees at Kotra Pharma Malacca and to ascertain the main determinants on demands of life insurance Besides that, this study is a quantitative research study whereby the findings of the study were analyzed by using the Statistical Package for the Social Sciences (SPSS). The data collected in this study is analyzed by using frequency, descriptive analysis; reliability, Pearson’s correlation analysis and multiple regressions in order to achieved the research objectives. Eventually, this study discovered that most of the respondents were male, Malay, married and most of them have a scale of household monthly income range between RM1000 to RM2000 and most of them have the insurance policy. In addition, multiple regressions also answered the research objective one where Based on the findings of beta value from each independent it shows that education level is the most influential determinants to the demands of life insurance. It is because education level obtained the highest beta which is 0.302 and P value is 0.000 which lower than 0.05. This means that independent variables of the education level are most significant and could be used as the best predictor to influence demands of life insurance in this study.